(untitled) (Al-Aasar, 2025)
This abstract provides an analysis of the causes and potential solutions for child labour in the Sargodha District. The identified root causes include poverty, limited access to education, and cultural norms that perpetuate the cycle of exploitation. To effectively address this issue, a multi-faceted approach is recommended. This includes implementing poverty alleviation programs to provide financial support to vulnerable families, enhancing access to quality education to ensure children have alternative opportunities, and enforcing labour laws rigorously to protect children from exploitation. Community engagement and awareness-raising campaigns are also crucial to changing societal attitudes towards child labour. By implementing these strategies, Sargodha District can create a safer and more conducive environment for children to thrive, free from the burden of exploitation, and with access to opportunities for holistic development.